Il cinema come macchina da guerra. Loin du Vietnam (1967) - Calabrò, Irene (Mechane, 2023)
The paper aims to analyse Loin du Vietnam (1967) as a “war machine”, investigating Godard’s Caméra-œil episode and the montage of the collective film, which combines fictional and documentary frames, to combat against the television war, images not allowing to think about Vietnam war.